(untitled) (AYUSHDHARA, 2017)
The classically Sciatic pain is distribute in pathway of Sciatic nerve. Herniated intervertebral disc is believed to cause most cases around 90% .Other lesions affecting the integrity of the lumbosacral nerve roots (L4-S3) or the sciatic nerve including lumbar canal or foramina, stenosis, tumors, cysts, hemorrhages, abscess, fractures and some more uncommon conditions may produce same clinical picture. The characteristic conditions of sciatica is most related to Gudrasi that mentioned in Ayurveda. Gudrasi Cikitsa under goes Vatavyadi Cikitsa . Chakradatta that mentioned bloodletting is effective for Vatavyadi. Jalaukavacharana is one of common method using for bloodletting in Ayurveda. Wet cupping is also procedure of bloodletting related with Alabu mentioned in Ayurveda. A comparative clinical study was designed with Group A of 20 patients being treated by Jalaukavacharana along and Group B of 20 patents with wet cupping along. The data analyzed individually with Sciatica Bothersomeness Index (SBI) and Sciatica Frequency index (SFI) and Compared using contingency coefficient and two way ANOVA. The results shows significant different between the groups with P value less than 0.001.There was highly significant with wetcupping group (B) dominating over Jalaukavacharana group(A). Though both Jalavkavacharana and Wet cupping provided relief, Wet cupping provided an acute and sustain relief.